Project PRIDE: A Cognitive-Behavioral Group Intervention to Reduce HIV Risk Behaviors Among HIV-Negative Young Gay and Bisexual Men. Issue 3 (August 2016) - Smith, Nathan Grant; Hart, Trevor A.; Moody, Chérie; Willis, Amy C.; Andersen, Marie Faaborg; Blais, Martin; Adam, Barry
Abstract: Young gay and bisexual men are at increased risk for human immunodeficiency virus (HIV) infection. Research suggests that the stress associated with being a stigmatized minority is related to negative mental health outcomes, substance use, and condomless sex. However, interventions aimed at reducing HIV risk behaviors in young gay and bisexual men have failed to address these important variables. The purpose of the present paper is to assist cognitive and behavioral therapists who work with young gay and bisexual men to conduct therapy for stress management and HIV prevention. This paper provides an overview of the research on stress and coping among gay and bisexual men and its relation with condomless sex among young gay and bisexual men. The treatment described here integrates minority stress theory (e.g., Meyer, 2003) and stress and coping theory (e.g., Lazarus, 2000) in a small group counseling framework that uses psychoeducation, cognitive reframing, and role plays to help young gay and bisexual men to manage stress, reduce substance use, and reduce condomless sex. The application of empirically supported theory and a combination of cognitive and behavioral techniques to reduce both psychological distress and HIV risk behavior for young gay and bisexual men is illustrated using three case examples. The present treatment may help therapists working with young HIV-negative gay and bisexual men who engage in condomless sex and who wish to remain HIV-negative by decreasing their HIV risk behavior. Highlights: Project PRIDE, an intervention for young gay/bisexual men, focuses on coping with minority stress to reduce HIV risk behavior. Case examples demonstrate participants' experiences in and outcomes of Project PRIDE. At 3-month follow-up, case examples reported no instances of unprotected anal intercourse. Project PRIDE appears to be a promising tool to reduce HIV risk among young gay and bisexual men. A randomized controlled trial could determine the efficacy of Project PRIDE at reducing HIV risk.